'Germany's salvation': Carl Schmitt's teleological history of the Second Reich. Issue 5 (4th July 2018) - Smeltzer, Joshua
ABSTRACT: Although Schmitt's enthusiastic conversion to National Socialism is well known, his short history of the German Kaiserreich, published in 1934, remains neglected in Anglophone scholarship. This article contextualizes Schmitt's narrative through the National Socialist conception of history and its accompanying teleology leading to the formation of the Third Reich. By placing Schmitt's historical text in conversation with his earlier Staat, Bewegung, Volk, this article argues that Schmitt appropriated the history of the Kaiserreich to construct liberalism as a social pathology which could only be cured through the 'concrete state theory' he outlined in Staat, Bewegung, Volk . Furthermore, this article argues that Schmitt's history relied heavily on propagandistic clichés of the Third Reich and thereby functioned as a rhetorical legitimation of Hitler's rise to power.